Źwa-deʼu ʼKhrul-źig Sprul-skuʼi miṅ gi rnam graṅs las draṅs paʼi gsol ʼdebs dam paʼi drin gyis smin paʼi dag snaṅ me tog ces bya ba bźugs so - Mdo-sṅags-bstan-ʼdzin-nor-bu, ʼKhrul-źig, 1923 or 4- (s.n., 1972)
Devotional verses recalling the various names and important events in the authorʼs spiritual life; composed at the behest of his disciples.